PELAKSANAAN PENILAIAN HASIL BELAJAR SISWA DALAM BIDANG STUDI PENJAS PADA SISWA TUNARUNGU SLB SE KOTA PEKANBARU: Performance Assessment of Student Learning Result in the Field of Penjas on Tunarungu SLB Students Kota Pekanbaru - Tity Hastuti; Merlina Sari; Mimi Yulianti (UIR Press, 2017)
Based on preliminary observations by the author at the School of extraordinary Se Pekanbaru to outcome assessment Learning PE, the implementation of the assessment of learning outcomes of students in the field of study of PE on the students Deaf SLB as the city of Pekanbaru on these students seen the attitude of student learning is not good, the first tendency in students showed serious attitude, playfulness and his lack of curiosity about the subject matter being taught penjasorkes, second, they tend to earn less than satisfactory learning outcomes, and third they tend to learn and practice if it will face a test. The method used is descriptive method, population in this study were all PE Teacher In SLB se Pekanbaru totaling 14 schools SLB. Sampling method in this research is purposive sampling, which is where most of the sampled population is numbered 6 PE teachers in special schools as the city of Pekanbaru. The reason for junior high school students with hearing impairment in SLB se Pekanbaru city exists only in 6 schools SLB. Data were analyzed by percentage. Interpreted on each aspect studied, namely: for the cognitive aspects of the overall criteria is or do not understand about the assessment of learning outcomes in the field of physical education studies, especially a lack of understanding of the assessment dlakukan teacher in junior high school students with hearing impairment. In the affective aspects both criteria or respondent has implemented penilaan learning outcomes as well without experiencing difficulties in meyuruh students respond to feedback given teacher in the learning process as part of the assessment for siswa.Aspek affective psychomotor criteria or teachers were not fully implement the system in the aspect ratings psychomotor well. Then aspects of remedial and enrichment with less criteria at all or has not done well, this dikarnakan fewer hours of lessons available.